We have to solve the equations 1/x=(y-1)/y and 3/x=(2y-1)/y

1/x=(y-1)/y

=> x = y/(y - 1)

Substitute x = y/ (y - 1) in 3/x=(2y-1)/y

=> 3/x=(2y-1)/y

=> 3 /[y/ (y - 1)] = (2y-1)/y

=> 3(y - 1)/y = (2y - 1)/y

=> 3y - 3 = 2y - 1

=> y = 2

x = 2/(2 - 1) = 2

**Therefore we get x = 2 and y = 2**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.